Endoscopic ultrasound, fine needle aspiration and cytology in patiens with suspected pancreatic cancer. Emphasis on negative predictive value / Salem Omar - Salem , Omar (2012)
Introduction: Endoscopic ultrasound (EUS) and EUS-guided fine needle aspiration (EUS-FNA) has greatly increased the sensitivity and specificity of pancreatic cancer diagnosis. However, few studies have dealt with the reliability of EUS and EUS-FNA in excluding pancreatic cancer. Aim: To study the reliability of EUS and EUS-FNA in excluding pancreatic cancer. Method: All patients with a suspicion of pancreatic cancer referred University Medical Centre Hamburg-Eppendorf, Hamburg, Germany for EUS from 2002 and 2003 were analysed. All these patients underwent EUS examination with a linear EUS system (GF UC140P-AL5; Olympus Optical Co., Ltd., Tokyo, Japan and SSD-5000, Aloka Co. Ltd., Tokyo, Japan) by 4 experienced examiners who had fulfilled the credentialing requirements as lined out by the American Society of Gastrointestinal Endoscopy (ASGE). The pancreas was examined systematically for signs of any lesions. If a focal lesion was imaged, EUS-FNA was performed with a 22G Echotip Ultra needle (Cook Medical, Winston-Salem, NC, USA). All patients were followed-up at hospitals or by telephone calls to the primary care doctors or the patients. Histological confirmation of pancreatic cancer would be obtained if patients underwent surgery. Detailed post-mortem reports were obtained from hospitals for patients who had passed away. When a final diagnosis of pancreatic cancer was made, documentary proof of this was obtained from the hospitals or primary care doctors. Results: 593 patients were recruited; 181 patients diagnosed by EUS-FNA with pancreatic cancer and 50 patients with cystic lesions were excluded from study. 412 iii patients with normal EUS findings or who were negative for malignancy by EUS-FNA were analysed (median age 60.9 years; 224M:188F). The median follow-up was 14 months (range 6-42). Patients without visible focal lesion (n=253) were further subdivided into those with ‗‗normal‘‘ pancreas [Group A] (n=122) and those with signs of chronic pancreatitis [Group B] (n=131). Patients with EUS-FNA negative focal ‗‗benign‘‘ lesions [Group C] (n=109) were further defined as either ‗‗circumscribed‘‘ [Group C1] (n=49), ‗‗non-circumscribed‘‘ [Group C2] (n=25) or ‗‗lobulated‘‘ [Group C3] (n=35). Nineteen (5.9%) patients were finally diagnosed with pancreatic cancer; none in group A, 2 (0.8%) in Group B and 17 (15.6%) in Group C ([Group A) vs. [Group C], [Group B] vs. [Group C] p<0.05). In the group C, 18.4%, 20% and 8.6% patients developed pancreatic cancer in the group C1, group C2 and group C3 respectively ([Group C1] vs. [Group C2] vs. [Group C] p=NS). The sensitivity, specificity, positive predictive value and negative predictive value of EUS in excluding PC in patients without any visible focal lesion were 98.9%, 100%, 100% and 99.2% respectively. The sensitivity, specificity, positive predictive value and negative predictive value of EUS-FNA in excluding PC in patients with ‗‗benign‘‘ focal lesions were 91.4%, 100%, 100% and 84.4% respectively. Conclusion: Pancreatic adenocarcinoma can be reliably excluded in patients with a normal EUS appearance. In the subset of patients with abnormal findings such as chronic pancreatitis and ‗‗benign‘‘ focal lesions, there is still a risk of malignancy and hence these patients should be closely followed-up.